PERLINDUNGAN HUKUM TERHADAP PEMILIK RAHASIA DAGANG YANG BERSIFAT KOMERSIL - Yanuarsi, Susi (Solusi, 2019)
Normative trade secrets are formulated as information that is not known to the public in the field of technology and / or business that has economic value because they are useful in business activities, and are kept confidential by the owners of trade secrets. Ownership and protection of confidential information that is categorized as trade secrets and is an intangible asset of the company, occurs automatically. Whoever discovers or makes this trade secret, it is automatically by law that he is considered to be the owner and this owner has the right to use or complain given a permit made by everyone for commercial support purposes